Nitrous Oxide Reduction Activity of Denitrifying Ochrobactrum anthropi Isolated from Rice Field - RATNA SETYANINGSIH; IMAN RUSMANA; PRIHASTO SETYANTO; ANTONIUS SUWANTO (Microbiology Indonesia, 2013)
Nitrous oxide (N2O) is one of the principal greenhouse gases. Differences in soil microbial community composition affect N2O emission. Ochrobactrum anthropi BL1 and BLN1 isolated from rice field in Tangerang, Banten, Indonesia can grow on and reduce N2O.  This study investigated  the patterns of N2O reduction activity and growth of O. anthropi BL1 and BLN1 on denitrification media and also examined the ability of BLN1 strain to reduce N2O in flooded rice soil. Nitrous oxide reduction activity and growth of strains BL1 and BLN1 occurred simultaneously, indicating that the bacteria used N2O for growth. BL1 and BLN1 showed the same specific growth rate, but the N2O reduction rate of BLN1 was higher than that of BL1. Increase of the N2O concentration in the surface water of flooded soil without BLN1 isolate six hours after the addition of NO3- was significantly greater than the surface water from soil that had been inoculated with the isolate.